Expression of recombinant amylase in Pichia Pastoris - Hazimah, Roslan (Universiti Malaysia Sarawak (UNIMAS), 2017)
Amylase is a hydrolytic enzyme that degrades starch. It is widely used in fermentation and food industries. Amylase can be found in many type of organism. Some organisms such as bacteria and fungi have extracellular enzymes secretion whereby it will secrete amylase from the cell. In this study, a recombinant amylase was transformed into yeast, Pichia pastoris, using the yeast vector, pPICZalpha. The aim of the study was to transform the recombinant amylase into P. pastoris using electroporation and to optimise the expression of the recombinant amylase using several inducing conditions. The optimisation of amylase activity was determined using DNS assay. Colony PCR was also used to check the integration of amylase in P. pastoris. Iodine staining was performed to observe protein expression after transformation. The production of recombinant amylase in yeast system have the potential to help in many application such as feedstock and food processing process.